UV-Induced Degradation Behaviour of HDPE, PET and NBR Films: An FTIR Analysis - Mohd Zulfikar, Zuhayra; Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2026)
This study investigates the ultraviolet (UV) degradation behaviour of high-density polyethylene (HDPE), polyethylene terephthalate (PET), and nitrile butadiene rubber (NBR) under controlled UV irradiation at 254 nm. Chemical changes induced by photo-oxidation were analysed using Fourier Transform Infrared (FTIR) spectroscopy. The formation of oxygen-containing functional groups, particularly carbonyl and hydroxyl groups, was used as an indicator of degradation. Results showed that HDPE exhibited early- stage oxidation and increased brittleness, while NBR underwent moderate degradation involving both chain scission and crosslinking. In contrast, PET demonstrated minimal chemical and physical changes, indicating superior UV resistance. These findings highlight the strong dependence of UV stability on polymer molecular structure.